Optimization Design of Single-Tuned Passive Filter Using Particle Swarm Optimization Algorithm in Industry - Malik, Mochamad Irlan; Hamdani, Yuda Muhammad; Yanti, Yanti (Teknik Elektro Universitas Siliwangi, 2025)
In the industrial sector, the widespread use of non-linear loads such as inverters and variable speed drives has led to increased harmonic distortion, which negatively impacts power quality. These harmonics can cause equipment malfunctions, overheating, reduced system efficiency, and potential failures in power infrastructure. This study aims to optimize the design of a Single-Tuned Passive Filter (STPF) using the Particle Swarm Optimization (PSO) algorithm to minimize harmonic distortion in industrial electrical systems. Harmonic measurements in a representative system revealed Total Harmonic Distortion of current (THDi) values of 20.2%, 20.3%, and 18.6% for phases L1, L2, and L3, respectively, with the 5th and 7th harmonic orders being the most dominant. Initial simulation using standard filtering reduced THDi to 3.03%, 3.10%, and 2.89%, but significant residual harmonics were still present. By applying a PSO-optimized STPF, the THDi was further reduced to 2.42%, 2.43%, and 2.23%, indicating a marked improvement in harmonic mitigation. These findings confirm that the PSO-based design approach effectively enhances filter performance, resulting in improved power quality, increased system reliability, and better protection of electrical equipment. The implementation of the optimized STPF is particularly valuable in industrial environments such as the automotive sector, where power stability and equipment longevity are critical.